Potato Physiological Disorders – Internal Heat Necrosis - Christine M. Worthington; Chad M. Hutchinson (EDIS)
HS-1145, a 3-page illustrated fact sheet by Christine M. Worthington and Chad M. Hutchinson, describes this physiological tuber disorder, IHN, that causes an unacceptable browning of the tuber tissue and can increase economic loss to the grower. Includes references. Published by the UF Department of Horticultural Sciences, June 2008.